Analisis Kritis Teori Manajemen Barat dengan Manajemen dalam Islam - Farid, Ahmad; Sarnoto, Ahmad Zain (Jurnal Manajemen dan Budaya, 2026)
The Western management paradigm, rooted in rationalism, empiricism, and materialism, tends to position humans as instruments of production oriented toward efficiency and material gain.  Meanwhile, the Islamic paradigm offers an integrative management concept that makes divine values ​​the basis of organizational management. This study aims to critically analyze Western management theory and Islamic management concepts to identify fundamental differences and emphasize the relevance of Islamic management as an alternative form of governance in the era of globalization. This study uses a literature review approach with a descriptive-critical analysis design. Data are sourced from the thoughts of Western management figures such as Henri Fayol and Peter F. Drucker, as well as Islamic normative sources such as the Qur'an and Hadith, which are analyzed using content analysis and interpretive techniques. The results show that Western management is anthropocentric and relatively value-free, while Islamic management is based on the principle of monotheism, making it theocentric and value-laden. The management function (POAC) from an Islamic perspective is not only technical, but also imbued with spirituality, emphasizing the balance between professionalism and belief in God, and is oriented towards welfare and the achievement of falah in this world and the hereafter.